Pengaruh Agresivitas Pajak Dan Growth Opportunity Terhadap Nilai Perusahaan Dengan Corporate Social Responsibility Sebagai Moderasi - Rakhmawati Oktavianna (Jurnal Akuntansi Keuangan dan Bisnis, 2021)
The value of a company can be influenced by several factors, including internal and external. This study uses internal factors, namely tax aggressiveness and Growth Opportunity, which aims to examine the effect on the value of a company with Corporate Social Responsibility as moderation. This study uses a sample of companies that are members of the National Center for Sustainability Reporting which are listed on the Indonesia Stock Exchange during the period 2014 to 2019. This type of research is quantitative research which uses secondary data. This study uses purposive sampling in determining the sample so that 60 data are obtained from 10 companies that issue annual reports and sustainability reports. The analysis technique uses multiple regression analysis and moderated regression analysis. In data processing using views 10. The results show that tax aggressiveness does not affect firm value, while growth opportunity affects firm value negatively. For the moderating variable, it shows that Corporate Social Responsibility cannot moderate the effect of tax aggressiveness on firm value but Corporate Social Responsibility can moderate growth opportunity on firm value.